2018
DOI: 10.1111/adb.12687
|View full text |Cite
|
Sign up to set email alerts
|

Stress responding and stress‐related changes in cue reactivity in heavy smokers, problem gamblers, and healthy controls

Abstract: Addictions, both substance and behavioral, have been conceptualized as involving similar biopsychosocial processes with different opportunistic expressions. A maladaptive stress response in combination with craving or urges to engage in the addictive behavior may be among the underlying factors common to behavioral and substance addictions. The current study compared the neuroendocrine (cortisol) and subjective responses to stress of gamblers and smokers to healthy controls. We assessed if participants respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…In addition to effects of gambling stimulation on cortisol levels, there are some studies attempting to investigate the impacts of acute stressors on the functioning of the HPA axis in individuals with gambling disorders. An early study showed a hypoactive HPA response to acute stressors induced by watching a video of gambling activity in pathological gamblers compared to recreational gamblers, regardless of gender (Paris et al, 2010b), while more recent studies failed to find a difference in the HPA response to social stress between individuals with gambling disorders and healthy controls (Arshad, 2018;Maniaci et al, 2018;Wemm et al, 2018). Since gambling itself can act as a stressor and has stress-like physiological effects (Buchanan et al, 2020), such evidence may indicate that effects of stress on the HPA response in gambling-addicted individuals is relatively specific to stressful events associated with gambling activity.…”
Section: Cortisol In Gambling/gambling Disordersmentioning
confidence: 99%
“…In addition to effects of gambling stimulation on cortisol levels, there are some studies attempting to investigate the impacts of acute stressors on the functioning of the HPA axis in individuals with gambling disorders. An early study showed a hypoactive HPA response to acute stressors induced by watching a video of gambling activity in pathological gamblers compared to recreational gamblers, regardless of gender (Paris et al, 2010b), while more recent studies failed to find a difference in the HPA response to social stress between individuals with gambling disorders and healthy controls (Arshad, 2018;Maniaci et al, 2018;Wemm et al, 2018). Since gambling itself can act as a stressor and has stress-like physiological effects (Buchanan et al, 2020), such evidence may indicate that effects of stress on the HPA response in gambling-addicted individuals is relatively specific to stressful events associated with gambling activity.…”
Section: Cortisol In Gambling/gambling Disordersmentioning
confidence: 99%
“…[50] In a study using biomarkers, the pattern of changes in salivary cortisol concentration in response to stress in heavy smokers was different from that of healthy adults and similar to that in gambling addicts. [51] From a different perspective, 1 study reported that when counseling, including interventions for stress, is conducted, the higher the counseling frequency, the higher the success rate of quitting smoking. [52] Therefore, for smokers complaining of high stress, long-term follow-up is necessary because the risk of smoking relapse is high even if smoking cessation is successful.…”
Section: Discussionmentioning
confidence: 99%
“…A second goal of the present study was to investigate whether the stress effects on the processing of SEM cues and SEM are moderated by indicators of problematic pornography use in generally healthy individuals. Assuming problematic pornography use shares underlying pathomechanisms with addiction, we hypothesized that changes in the reward system occur due to dysregulation of the stress system during the transition from recreational to addictive behavior as it has been shown in addiction research ( Koob & Schulkin, 2019 ; Piazza & Deroche-Gamonet, 2013 ; Wemm et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, less is known about the mechanism underlying the effect of acute stress on cue reactivity and craving in addictive individuals. A recent study showed that the effect of stress differed between addictions with increased craving in nicotine smokers but decreased craving in gamblers ( Wemm, Cao, Han, & Wulfert, 2020 ). Therefore, we aim at investigating whether the effect of stress on SEM processing depends on indicators of problematic pornography use.…”
Section: Introductionmentioning
confidence: 99%